A CLINICAL STUDY OF ORAL TE-031 (A-56268) IN RESPIRATORY INFECTIONS - KUDO, KOICHIRO; KABE, JUNZABURO; KOMASE, YUKO; KOWADA, AKIKO (CHEMOTHERAPY, 1988)
We studied the clinical efficacy and safety of TE-031 (A-56268) in 13 patients with respiratory infection (pneumonia 4, acute bronchitis 4, bronchopneumonia 1, mycoplasma pneumonia 1, lung abscess 1, middle lobe syndrome 1, and exacer bated bronchiectasis 1), who were treated with oral TE-031 at a daily dose of 200mg, 400mg or 600mg for 6-21 days. Overall clinical efficacy was 76.9%(10/13): good in 10 cases and fair in 3. No clinical side effect was observed. A slight increase in serum GPT level in one case was the only abnormal laboratory finding.